The Ohlson (1995) Model and Stock Return - DEWA GEDE WIRAMA (The Indonesian Journal of Accounting Research, 2013)
This research reexamines the ability of Ohlson (1995) valuation model in predicting stock return. Empirical specifications of the model in previous researches violated the model assumptions regarding the nature of model's parameters, discount factor, and the clean surplus relation. Those violations undermine the validity of the researches' conclusions regarding the model.Two portfolios are formed based on the ratio between stock values as calculated by Ohlson Model and market prices, both in relative and absolute terms. In relative term, stocks with relatively high ratio are considered to be undervalued and therefore command a higher return, and vice versa. In absolute term, a stock is considered to be undervalued if the ratio is greater than one.Return prediction is based on a buy-and-hold strategy for one to eight years investment periods. Using a sample of 96 companies listed in the Indonesian Stock Exchange, providing a total of 768 firm-year observations, it is found the Ohlson Model can predict return only in relative term but not in absolute term. Consequently, an investor who wishes to utilize the model in forming stock portfolio must calculated the value of each company listed in the stock market, and buy those stocks that are relatively undervalued compared to the overall market valuation.